Business driven technology - Baltzan, Paige (McGraw Hill, 2022)
"Unlike any other MIS text, Business Driven Technology, 9e, discusses various business initiatives first and how technology supports those initiatives second. The premise for this unique approach is that business initiatives should drive technology choices. Every discussion in the text first addresses the business needs and then addresses the technology that supports those needs."--Provided by publisher.